Growing Barley and its Medicinal Properties - Ma’muraxon, Atabayeva; o‘gli, To‘xtasinov Odiljon Nurmuxammad (American Journal of Biology and Natural Sciences, 2024)
This article analyzes the cultivation of barley and its medicinal properties. Barley is a widespread and highly productive agricultural crop, which requires the introduction of new agricultural technologies and cultivation methods. The medicinal properties of barley are considered, as well as its use in folk medicine, especially for the treatment of diseases of the gastrointestinal tract, cardiovascular system and strengthening the immune system.